Magnetism, magnetocaloric and magnetodielectric properties of DyVWO6: a new aeschynite-type polar antiferromagnet. (12th February 2020) - Yanda, Premakumar; Sundaresan, A
Abstract: We report magnetic, magnetocaloric and magnetodielectric properties of a new polar magnet DyVWO6 crystallizing in the orthorhombic structure ( Pna 21 ). It consists of edge-shared dimers of VO6 and WO6 octahedra, which are connected by corner-sharing to a form three-dimensional network structure with Dy 3+ cations located in the channels. The ordering of V 3+ and W 6+ ions in the octahedral sites breaks the inversion symmetry of the parent-CaTa2 O6 structure ( Pnma ). Magnetic and heat capacity measurements show that the V 3+ and Dy 3+ ions undergo antiferromagnetic transitions at T N V ∼ 5 K and T N D y ∼ 2.5 K, respectively. Isothermal magnetization shows a metamagnetic transition at the applied magnetic field of 1 T at 2 K that corresponds to a transition from the antiferromagnetic (AFM) to ferromagnetic (FM) spin structure. Further, this compound exhibits significant magnetocaloric effect (MCE) with a maximum magnetic entropy change (−∆ S M max ) of 8.45 J Kg −1 K −1 at 7 T. In addition to this, we observe a drop in dielectric constant below T N V with a low temperature dielectric relaxation.